Gilbert A. Harrison papers - Harrison, Gilbert A.; Harrison, Anne Blaine, 1918-1977.
Correspondence, subject files, clippings, pamphlets, articles, and other papers relating principally to Harrison's position as editor and publisher of the New Republic and as president of Liveright Publishing Corporation. Persons and topics represented include Dean Acheson, Joseph Alsop, American Civil Liberties Union, American Veterans Committee, Roger N. Baldwin, Saul Bellow, Anita McCormick Blaine, Jimmy Carter, Frank Church, Malcolm Cowley, Felix Frankfurter, J. William Fulbright, John Kenneth Galbraith, Ernest Gruening, Francis Hackett, Lillian Hellman, Irving Howe, Hubert H. Humphrey, Lyndon B. Johnson, Edward M. Kennedy, John F. Kennedy, Anthony Lewis, Walter Lippmann, Eleanor Roosevelt, Bertrand Russell, William Saroyan, Arthur M. Schlesinger, Jr., Gertrude Stein, Adlai E. Stevenson, and Morris K. Udall. Also includes correspondence and other papers of Harrison's wife, Anne "Nancy" Blaine Harrison, relating in part to her activities as an organizer for the Textile Workers Union of America in North Carolina in the 1940's and to Washington, D.C., social life.
Editor and publisher. Full name: Gilbert Avery Harrison. Born 1915. Died 2008.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971.; Alsop, Joseph, -- 1910-1989.; Baldwin, Roger N. -- 1884-1981.; Bellow, Saul; Blaine, Anita McCormick; Carter, Jimmy, -- 1924-; Church, Frank; Cowley, Malcolm, -- 1898-1989.; Frankfurter, Felix, -- 1882-1965.; Fulbright, J. William -- 1905-1995.; Galbraith, John Kenneth, -- 1908-2006.; Gruening, Ernest, -- 1887-1974.; Hackett, Francis, -- 1883-1962.; Hellman, Lillian, -- 1905-1984.; Howe, Irving; Humphrey, Hubert H. -- 1911-1978.; Johnson, Lyndon B. -- 1908-1973.; Kennedy, Edward M. -- 1932-2009.; Kennedy, John F. -- 1917-1963.; Lewis, Anthony, -- 1927-2013.; Lippmann, Walter, -- 1889-1974.; Roosevelt, Eleanor, -- 1884-1962.; Russell, Bertrand, -- 1872-1970.; Saroyan, William, -- 1908-1981.; Schlesinger, Arthur M. -- 1917-2007.; Stein, Gertrude, -- 1874-1946.; Stevenson, Adlai E. -- 1900-1965.; Udall, Morris K; American Civil Liberties Union; American Veterans Committee; Liveright Publishing Corporation; Textile Workers Union of America; New republic; American periodicals; Periodicals -- Publishing; Labor unions -- North Carolina; Washington (D.C.) -- Social life and customs; Editors; Publishers